Tratamiento de los sub-productos del cafe en el beneficiado hémedo en la Región VI de Nicaragua - Orozco S, C.=700 1 Cantarero P, V.; Waáer, R.; Rodríguez, J.F.; Rustrián M, E.
Sumario (Es)
Ilus.
Keywords: CAFE; SUBPRODUCTOS; BENEFICIO BRUTO; DESECHOS SOLIDOS; OXIDACION; NICARAGUA